Proceedings of the International Conference on Bio-Inspired Systems and Signal Processing 2015
DOI: 10.5220/0004998201190125
|View full text |Cite
|
Sign up to set email alerts
|

ECG Denoising based on PCA and using R Peaks Detection

Abstract: In this paper, we propose a new Electrocardiogram (ECG) Denoising technique based on Principal Component Analysis (PCA) and using R peaks detection. This technique consists at first step in cutting the entire ECG signal into frames then the denoising is performed frame by frame by using PCA. Each frame is located between two successive R peaks. The R peaks detection is performed by using a new detection method based on multi-scale product of the undecimated wavelet coefficients. The Reconstructed ECG signal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…AthrIA was tested in both simulated and experimental 10 s ECG signals (sampling frequency: 250 Hz), preprocessed using a technique based on the principal component analysis (only the first eigenvector projection was used) [13,14]. R peaks were detected through the Pan-Tompkins algorithm [1].…”
Section: Datamentioning
confidence: 99%
“…AthrIA was tested in both simulated and experimental 10 s ECG signals (sampling frequency: 250 Hz), preprocessed using a technique based on the principal component analysis (only the first eigenvector projection was used) [13,14]. R peaks were detected through the Pan-Tompkins algorithm [1].…”
Section: Datamentioning
confidence: 99%
“…Recently, a research reported that combination of EEMD and PCA techniques applied to a PPG to monitor heart rate (HR) and RR yielded a good result [23]. Other researchers used PCA as a tool to reduce ECG noise [24].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem, many scholars have proposed various methods. Among all the methods, template‐based techniques [1, 2] and principle component analysis [3–5] denoise method are often used; however, both methods work only when R peak has been detected in processing single lead ECG. Therefore, filter‐based [6, 7] method, empirical mode decomposition [8, 9] and wavelet transform (WT) [10, 11]‐based method are developed.…”
Section: Introductionmentioning
confidence: 99%